IDENTIFIKASI POTENSI JABON MERAH (ANTHOCEPHALUS MARCOPHYLLUS) DI KECAMATAN BUA KABUPATEN LUWU - Dhiki Efendi; Andi Rosdayanti; Afandi Ahmad (Jurnal Penelitian Kehutanan BONITA, 2019)
Community forest is one model of natural resource managements based on community initiatives. The development of community forests is directed at restoring land productivity. Scarcity of industrial wood raw materials requires fast-growing commercial wood, jabon merah is a fast-growing plant. Potential of jabon merah at Bua District has not been known certainly. Inventory studies contain descriptions of forested areas and potential assessments. Bua sub-district is one of the sub-districts producing jabon merah wood that comes from community forests. This research was conducted from August to September 2019 with the aim to find out how much the potential for jabon merah and the distribution of jabon merah are in Bua sub-district. This research was conducted by quantitative description method. the results obtained by an inventory of the potential of jabon merah in Bua sub-district are 5,127 m3. Volume of jabon merah for each diameter class is 0.99 m3 for the diameter class of 5-10.99 cm, 277.60 m3 for the diameter class of 11-19.99 cm, 338.20 m3 for the diameter class of 20-29.99 cm, and 122.15 m3 for the widest class located in the village of Tiromanda with 11 stands of jabon merah stands, witharea of 5.3 ha.The lowest and lowest distribution is located in Lare-Lare village, only 1 area of jabon merah stands, with an area of 0.8 ha.Keywords: Forest of the people, Potential, Distribution, Jabon Merah.